Dark music - Lagercrantz, David (Alfred A. Knopf, 2022)
"Summer 2003: A soccer referee -- an immigrant from war-torn Afghanistan -- is found dead after a youth match in a Stockholm suburb. The father of one of the players, who had threatened the ref, is quickly arrested, but he protests his innocence. The police decide to consult Professor Hans Rekke, a world-renowned authority on interrogation and prisoner confessions. Things do not proceed as planned as Rekke challenges the team's assumptions and demolishes their case. The suspect is released, and the police find themselves out of leads. Only Micaela Vargas, a young officer from an immigrant family and with brothers who make a living on the other side of the law, refuses to let the matter rest, unable to forget the ref's strange behaviour in his last game. She tries to consult Rekke again, but the professor seems to have dropped off the radar. A year later, a chance encounter establishes an instant bond between these two very different characters. Rekke's world has changed, but Vargas enlists him to help solve the dormant case, and they soon find themselves uncovering connections between Sweden and the American "war on terror" in Afghanistan. But was the murdered referee a victim or a perpetrator? And why is the CIA -- and Rekke's own powerful brother -- determined to thwart the pair at every turn?"--